Gallstone Disease and the Risk of Type 2 Diabetes. Issue 1 (December 2017) - Lv, Jun; Yu, Canqing; Guo, Yu; Bian, Zheng; Yang, Ling; Chen, Yiping; Li, Shanpeng; Huang, Yuelong; Fu, Yan; He, Pan; Tang, Aiyu; Chen, Junshi; et al.
Abstract Gallstone disease (GSD) is related to several diabetes risk factors. The present study was to examine whether GSD was independently associated with type 2 diabetes in the China Kadoorie Biobank study. After excluding participants with prevalent diabetes and prior histories of cancer, heart disease, and stroke at baseline, 189, 154 men and 272, 059 women aged 30–79 years were eligible for analysis. The baseline prevalence of GSD was 5.7% of the included participants. During 4, 138, 687 person-years of follow-up (median, 9.1 years), a total of 4, 735 men and 7, 747 women were documented with incident type 2 diabetes. Compared with participants without GSD at baseline, the multivariate-adjusted hazard ratios (HRs) for type 2 diabetes for those with GSD were 1.09 (95% CI: 0.96–1.24; P = 0.206), 1.21 (95% CI: 1.13-1.30; P < 0.001), and 1.17 (95% CI: 1.10-1.25; P < 0.001) in men, women, and the whole cohort respectively. There was no statistically significant heterogeneity between men and women (P = 0.347 for interaction). The association between GSD and type 2 diabetes was strongest among participants who reported ≥5 years since the first diagnosis and were still on treatment at baseline (HR = 1.48; 95% CI: 1.16-1.88; P = 0.001). The present study highlights the importance of developing a novel prevention strategy to mitigate type 2 diabetes through improvement of gastrointestinal health.